2015
DOI: 10.1371/journal.pone.0132115
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 as a Prognostic Biomarker in Ruptured Intracranial Aneurysms

Abstract: BackgroundInterleukin-6 (IL-6), a proinflammatory cytokine, was found to surge in the cerebral spinal fluid after aneurysmal subarachnoid hemorrhage (SAH). We hypothesized that the plasma level of IL-6 could be an independent biomarker in predicting clinical outcome of patients with ruptured intracranial aneurysm.MethodsWe prospectively included 53 consecutive patients treated with platinum coil embolization of the ruptured intracranial aneurysm. Plasma IL-6 levels were measured in the blood samples at the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Inflammation mediated by IL-1 is increasingly recognized as an important contributor to neurodegeneration after acute cerebrovascular events. Al- 20,30,37 We demonstrated previously that IL-1 antagonism using IV anakinra is a safe and effective way to reduce IL-6 following cerebral ischemic stroke 7 and SAH. 32 In this study, we have proven that administration of SC IL-1Ra, starting within 72 hours and continued for a maximum period of 21 days postictus, is safe and significantly reduces plasma concentrations of IL-6 following aSAH.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammation mediated by IL-1 is increasingly recognized as an important contributor to neurodegeneration after acute cerebrovascular events. Al- 20,30,37 We demonstrated previously that IL-1 antagonism using IV anakinra is a safe and effective way to reduce IL-6 following cerebral ischemic stroke 7 and SAH. 32 In this study, we have proven that administration of SC IL-1Ra, starting within 72 hours and continued for a maximum period of 21 days postictus, is safe and significantly reduces plasma concentrations of IL-6 following aSAH.…”
Section: Discussionmentioning
confidence: 97%
“…IL-6 binding to a soluble IL6R (sIL6R) complex with ubiquitously expressed membrane-bound signaling protein gp130 can initiate pro-inflammatory signaling in cells that do not express IL6R [ 30 ]. Increased systemic and local tissue expression of IL-6 has been well-characterized in clinical studies of IA, and although some suggest that lower IL-6 levels are synonymous with lower rates of IA rupture [ 31 , 32 ], other studies have shown that certain polymorphisms in the IL-6 gene can be protective against IA [ 33 ]. A meta-analysis of IA in a Southern Indian population showed that genetic variants in TNF and IFNγ but not IL-6 were associated with IA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standard endovascular procedures and adjunctive therapies were detailed in our previous study. 21 In addition to recording the aneurysmal location, number, size, and morphology, the neuroradiologist gauged the vasospasm grade, on a scale of 0 to 4. 22…”
Section: Methodsmentioning
confidence: 99%